Event-Based Control of Constrained Discrete-Time Linear Systems with Guaranteed Performance - Watkins, Benjamin; Al-Areqi, Sanad; Reimann, Sven; Liu, Steven (International Journal of Sensors Wireless Communications and Control, 2015)
This paper addresses event-based control design problem for discretetime linear systems subject to input and state constraints with guaranteed performance measured by an assigned quadratic cost function. Instead of considering a model-predictive controller (MPC) and a given event-triggering condition as usually proposed in literature, a codesign problem of the control parameters and the event-triggering parameters is formulated as a linear matrix inequality optimization problem with the objective of maximizing the domain of attraction. The effectiveness of the proposed codesign strategy is evaluated for networked control of an inverted pendulum mounted on a cart and compared with an existing event-based MPC strategy in literature.
Keywords: Model predictive control